Histological findings in skeletal muscle of SARS-CoV2 infected patient. Issue 6 (1st November 2020) - Mageriu, Vlad; Zurac, Sabina; Bastian, Alexandra; Staniceanu, Florica; Manole, Emilia
ABSTRACT: Autopsies represent medical procedures through which the causes of patients' deaths are determined or, through tissue sampling and microscopic examination of slides in usual stains or special tests, one can offer the basis for understanding the physiopathological mechanisms that contribute to the patients' death Histological findings of tissue samples from patients who have died of COVID-19 have been mainly orientated to lung, heart, liver, kidney damage with a small percent of them following other organs, but none has, to our knowledge, studied skeletal muscle.